The Euro Area Government Spending Multiplier in Demand- and Supply-Driven Recessions? - Mario Di Serio; Matteo Fragetta; Emanuel Gasteiger; Giovanni Melina (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2023)
Road infrastructure has been a key input in the economic growth and poverty reduction strategies of China and India. The two countries have used very different instruments for road financing with China mobilizing substantial resources through directed credit by state-owned banks and India heavily relying on international institutions and fuel taxes. However, current modalities of road financing will be insufficient to meet future investment needs requiring both countries explore new mechanisms to attract private capital and expand the fiscal space of central and subnational governments. Different instruments of resource mobilization and intermediation are assessed and compared extracting lessons that could be valuable to many developing countries. Facilitating the participation of the private sector in road development would require inter alia strengthening regulatory frameworks and deepening and broadening domestic financial markets. But given the strong public good characteristics of large segments of the road networks in China and India most of the funding for road construction and maintenance would need to come from the establishment of efficient and sustainable systems of earmarked road-related charges, including a fuel tax in China.We estimate government spending multipliers in demand- and supply-driven recessions for the Euro Area. Multipliers in a moderately demand-driven recession are 2-3 times larger than in a moderately supply-driven recession, with the difference between multipliers being non-zero with very high probability. More generally, multipliers are inversely correlated with the deviation of inflation from its trend, implying that the more demand-driven a recession, the higher the multiplier. Median multipliers range from -0.5 in supply-driven recessions to about 2 in demand-driven recessions. The econometric approach leverages a factoraugmented interacted vector-autoregression model purified of expectations (FAIPVAR-X). The model captures the time-varying state of the business-cycle including strongly and moderately demand- and supply-driven recessions, by taking the whole distribution of inflation deviations from trend into account.
Keywords: C32; C33; C38; E32; E62; 330; Fiscal Multiplier; Business Cycle; Interacted Panel VAR; Factor Models; Euro Area